KEMAMPUAN Azetobacter sp. DALAM MENINGKATKAN EFISIENSI PEMUPUKAN UREA PADA TANAMAN JAGUNG (Zea mays L.) - Nur Winda Rachmadhani; Didik Hariyono; Mudji Santoso (Universitas Tribhuwana Tunggadewi, 2018)
Azotobacter sp. is a non-symbiotic bacteria that has the ability to mobilize nitrogen from a form that is not available in a form that is available for plants. Inoculation of Azotobacter sp. into the planting medium can be used as a supplier of nitrogen required by the plant. Utilization of Azotobacter sp. as biofertilizer has the ability to minimize the use of chemical fertilizers, improve the soil fertility and increase the microbial activity in the rhizosphere of plants. Inoculation of Azotobacter sp. into the planting medium is one alternative to improve the efficiency of urea fertilizer in the maize cultivation. The result of this research showed that the application of Azotobacter sp. with the dose of 10 ml l-1 and 20 ml l-1 on the urea fertilization with the dose of 150 kg ha-1 were able to increase the growth of maize, so that maize has growth that was not significantly different with the maize that got urea with the dose of 225 kg ha-1 and 300 kg ha-1. Inoculation of Azotobacter sp. in the planting media, either with the dose of 10 ml l-1or 20 ml l-1were able to increase the maize yield when compared to the treatment without Azotobacter sp. Inoculation of Azotobacter sp. into the planting medium was able to increase the maize yield. However, increasing the dose of Azotobacter sp. more than 10 ml l-1 did not affect to increase the maize yield. Maize yield reached the optimum value when the dose of urea supplied was153.50 kg ha-1.